Mobbing At Elementary Schools In Turkey - Gökçe, Asiye Toker (Mediterranean Journal of Social Sciences, 2012)
This paper introduces the concept of mobbing in education system in Turkey. The aims of the study were; to define negativeacts causing mobbing at schools; to assess relationships between mobbing and school type, gender, age, job experience, and teachers’branch; and to investigate reasons for mobbing at schools. A theoretical framework based on the literature was proposed. Afterwards, anexploratory survey was formed to gather essential data for the study. T-test and ANOVA were utilized for analyzing the data. Thefindings reveal that teachers are subject to mobbing at schools. There are high correlations between mobbing and school type andprofessional experience at schools. Yet there are slight relationships between mobbing, gender, and age. Both school administrators andcolleagues mob teachers. The study contributes significant information and data for further research about mobbing at schools in thenational and international level.